Nānnanz or Larri at Shāradā: Specimens of Human Habitat and Aesthetics of the Neelam Valley - Khan, Mamoona; Khan, Rukhsana; Abbas, Nausheen (Ancient Pakistan, 2019)
Larri, the wooden houses are manmade habitat of the Neelam Valley (Azad Kashmir), justify their being environment friendly, for having capacity to protect from the natural hazards. The efficacy of these structures lies in their inherent earthquake resistant properties. Wooden structures are basically timber based frames, which have proved to be popular all over the world in the earthquake prone areas. An example is the earthquake of 2005, which approved this along with protection of wooden structures from the extreme weathering conditions. These are so planned that the entire needs of these people could be catered, even with changing conditions of seasons. Furthermore, the wooden dwellings skilfully maintain kitchens and washrooms, though wood is vulnerable to fire and water. Aesthetically these houses are not simple, rather adorned with carvings. Lovely motifs are carved on various parts of the structures, whether inhabited by simple or by sophisticated class. The research will be an onsite study of wooden houses of Shāradā, in the Neelam Valley, locally called Larri or Nānnanz. The analysis of structural and functional values of the wooden houses is made and recommendations proposed.